A systematic analysis of occupational health and safety implementation in reducing accident risks on drilling rigs through risk control strategies: A review article - Rozi Mexiwel; Heri Wardana; Achmad Jusuf Zulfikar (LPPMPK- Universitas Muhammadiyah Cileungsi, 2025)
This article presents a systematic review of the implementation of Occupational Health and Safety (OHS) systems in oil and gas drilling operations, with a particular focus on risk control strategies. The high-risk nature of drilling activities demands a proactive and comprehensive approach to managing safety hazards, which include toxic gas exposure, high-pressure fluid systems, and harsh working environments. Drawing upon studies published between 2018 and 2024, the review evaluates the effectiveness of international standards such as ISO 45001, Indonesia’s SMK3, and OSHA's Process Safety Management in mitigating workplace accidents. Key findings indicate that structured application of these systems, supported by top management commitment, continuous training, and active worker participation, significantly reduces accident rates. The review also highlights the importance of the hierarchy of controls and the integration of Internet of Things (IoT)-based monitoring technologies in enhancing real-time hazard detection. However, several implementation challenges persist, including inconsistent procedural adherence, insufficient competency-based training, and weak reporting cultures. To address these issues, the study recommends regular evaluations, external audits, and strengthened safety culture initiatives. Overall, this review contributes to a deeper understanding of OHS performance in high-risk drilling environments and provides evidence-based recommendations to improve workplace safety and operational sustainability in the oil and gas sector.